SYSTEMATIC LITERATURE REVIEW: IMPLEMENTATION OF ORGANIZING KNOWLEDGE AT COLLEGE LIBRARY IN INDONESIA - Rikka Poerna Anggelia; Tamara Adriani Salim (JURNAL ILMU PERPUSTAKAAN (JIPER), 2023)
The application of organizing knowledge in libraries is very important for the development and performance of a library. This study aims to provide a study and analysis of the application of organizing knowledge in university libraries in Indonesia. The methodology of systematic literature review is carried out in this qualitative descriptive study to describe and examine in detail several written works or articles. The collection of article material is carried out through searches on the ResearchGate portal for articles relevant to the specified topic. Further more, the articles were framed and selected through several exclusion and inclusion selection. The results of this study indicate that most of the research related to the application of organizing knowledge is carried out through qualitative methods. The models and methods of implementing organizing knowledge also vary according to the conditions and perspectives of each university library.